2022
DOI: 10.1111/1759-7714.14612
|View full text |Cite
|
Sign up to set email alerts
|

Dietary acid load and esophageal cancer risk: A case‐control study

Abstract: Background: A high dietary acid load (DAL) can produce metabolic acidosis, which is linked to cancer development through mechanisms of inflammation and cell transformation. There is limited epidemiological evidence linking DAL and cancer risk; however, none of the published studies focused on DAL and esophageal cancer (EC) risk in particular. Therefore, we sought to explore this association in the present study. Methods: A case-control study was performed in 1295 male patients (185 squamous cell EC cases and 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(36 citation statements)
references
References 63 publications
6
30
0
Order By: Relevance
“…However, the two latter scores were not significantly associated they tended to increase the odds. These different results were also shown in the previous research 19,39,40 . A case-control stusy by Ronco et al showed that the highest versus lowest quartile of the PRAL score but not the NEAP score significantly increased the risk of colorectal cancer 39 .…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…However, the two latter scores were not significantly associated they tended to increase the odds. These different results were also shown in the previous research 19,39,40 . A case-control stusy by Ronco et al showed that the highest versus lowest quartile of the PRAL score but not the NEAP score significantly increased the risk of colorectal cancer 39 .…”
Section: Discussionsupporting
confidence: 71%
“…These different results were also shown in the previous research 19,39,40 . A case-control stusy by Ronco et al showed that the highest versus lowest quartile of the PRAL score but not the NEAP score significantly increased the risk of colorectal cancer 39 . A researcher also found similar results in a cross-sectional study of 3,501 Chinese participants on the association between dietary acid load and odds of hypertension 19 .…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Eight studies (Park et al , 2019; Mehranfar et al , 2020; Nasab et al ., 2021; Ronco et al , 2020; Safabakhsh et al , 2020; Ronco et al, 2021a,b; Shi et al , 2021) reported diet acidity load as PRAL, seven (Park et al , 2019; Mehranfar et al , 2020; Ronco et al , 2020; Safabakhsh et al , 2020; Ronco et al, 2021a,b; Shi et al , 2021) as NEAP, two as NAE (Wright et al , 2005; Park et al , 2019) and one as A:P (Park et al , 2019). All studies used a food frequency questionnaire for dietary assessment.…”
Section: Resultsmentioning
confidence: 99%
“…DAL-induced low-grade mild metabolic acidosis promote tissue damage and inflammation (11,13,117,118) , which may initiate genomic instability on normal cells through the activation of cytokines, which may stimulate tumour invasion and metastases (119,120) . Positive associations between a high DAL and various cancers have been reported, including breast cancer (121,122) , prostate cancer (123) , lung cancer (124) , colorectal cancer (125) , pancreatic cancer (126) , gastric cancer (127) , oesophageal cancer (128) as well as head and neck cancers (129) . Two meta-analyses confirmed these associations: Keramati et al and Bahrami et al independently found higher odds for cancer in individuals with elevated DAL scores (130,131) .…”
Section: Introductionmentioning
confidence: 99%